Exploring Cloud-Based Materials as Authentic and Relevant Models for Teaching Lexicogrammar - Barans I. Palangan (English Language and Education Spectrum, 2021)
Teaching English, particularly teaching its lexicogrammatical concepts, has been a challenging problem for teachers in Indonesia during this pandemic. The 'new normal' era has forced teachers to find cloud-based lexicogrammar materials for modeling activities in their online classes. These lexicogrammar materials are fortunately abundant on the internet, yet teachers, who are not English native speakers, still must search for authentic and relevant models. The purpose of this research, therefore, is to explore and present authentic and relevant cloud-based English lexicogrammar materials that can be good models for Indonesian teachers. In this exploratory study, both online and literature types of research were conducted to answer the formulated hypothetical question, "Does the internet really provide English teachers with authentic and relevant cloud-based materials for lexicogrammar modeling?" The result showed that so far, there are at least four websites providing authentic and relevant cloud-based English lexicogrammar materials for modeling activities in distance learning. Moreover, these four cloud-based materials provide free and easy access for internet users and various materials such as quizzes, videos, and downloadable materials; hence, good models for Indonesian English teachers. This research, moreover, also found that in terms of cloud-based materials, not only can internet-based materials be used as authentic and relevant materials, but even the 'offline' computer based-materials, which have been familiar among teachers before the pandemic, can also be authentic, relevant, and compelling cloud based-materials with the help of the common online platforms such as Zoom or Google Apps.